2014
DOI: 10.1371/journal.pone.0108224
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Orienting to Pictures with and without Humans: Evidence from the Cardiac Evoked Response (ECR) and the Cortical Long Latency Parietal Positivity (LPP)

Abstract: ObjectiveThis study investigated the effect of social relevance in affective pictures on two orienting responses, i.e. the evoked cardiac response (ECR), and a long latency cortical evoked potential (LPP) and whether this effect would differ between males and females. Assuming that orienting to affective social information is fundamental to experiencing affective empathy, associations between self-report measures of empathy and the two orienting responses were investigated.MethodECRs were obtained from 34 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…Participants watched a series of 414 photographs that had been selected from the International Affective Picture System (IAPS) (Lang et al 2008 ), representing the following conditions: neutral, positive or negative emotions in scenes with humans (socially relevant conditions); or neutral, positive or negative emotions in scenes without humans (socially irrelevant conditions, see Groen et al ( 2013 ) or Althaus et al ( 2014 , 2015 )). By using E-prime 2.0, the pictures were serially presented for 1 s with a variable inter-stimulus interval of 3 to 5 s and required no response.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants watched a series of 414 photographs that had been selected from the International Affective Picture System (IAPS) (Lang et al 2008 ), representing the following conditions: neutral, positive or negative emotions in scenes with humans (socially relevant conditions); or neutral, positive or negative emotions in scenes without humans (socially irrelevant conditions, see Groen et al ( 2013 ) or Althaus et al ( 2014 , 2015 )). By using E-prime 2.0, the pictures were serially presented for 1 s with a variable inter-stimulus interval of 3 to 5 s and required no response.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, by using SPSS, for each participant, the maximal cardiac deceleration was determined in the interval from −0.5 to 4 s (IBI MAX ). For the validity of this measure, we refer to Althaus et al ( 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported significant effects of the social content (human vs. non-human) of emotional stimuli on the reactivity at central level, through evoked potential analysis ( Proverbio et al, 2009 ; Groen et al, 2013 ) and at peripheral level, through autonomic measures ( Althaus et al, 2014 ; Singleton et al, 2014 ). This social effect has been related to an automatic attentional affective processing, which facilitates the empathy ( Proverbio et al, 2009 ; Groen et al, 2013 ) or social abilities ( Althaus et al, 2014 ; Singleton et al, 2014 ). In this line, Singleton et al (2014) , found higher values of SCRs for social relevant stimulus than for those without social relevance, in healthy participants scoring high in autistic symptoms scale.…”
Section: Introductionmentioning
confidence: 99%
“…Also, children's gender was considered as a possible significant factor in modulating emotional responses. In fact, many previous studies have reported consistent evidence of sex differences in emotional reactivity to affective pictures, with women generally showing stronger physiological reactions to especially negative, aversive pictures (Althaus et al, 2014) and more distress to fearful and stressful experiences (Kudielka, Buske-Kirschbaum, Hellhammer, & Kirschbaum, 2004). Such effects have also been replicated in laboratory ecological stress-related tasks.…”
Section: Introductionmentioning
confidence: 77%